Pengembangan Program Green-Posdaya dalam Rangka Peningkatan Kualitas Pemberdayaan Masyarakat - Pudji Muljono; . Saharuddin (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2015)
The purpose of this activity is to develop a Green-Posdaya programe to improve the quality of community empowerment, especially in the fields of economics, education, health, and the environment. The program is implemented in five villages in the District Klapanunggal, Bogor Regency, whose synergy between professional course work (KKP) IPB student partnership programe through CSR activities of PT. Holcim indonesia, Tbk. In the first year has been realized several achievements that are still pioneering activities and mentoring beginning, namely the development of Green-Posdaya, improved management of early childhood education, and strengthening microfinance institutions. It is expected that the activities of the next period, gradually achieved healthier living conditions and welfare of local communities.